Circulating Plasma miRNA-21 as a Superior Biomarker Compared to CA 15-3: Assessment in Healthy Age Matched Subjects and Different Stage of Breast Cancer Patients - Merlyna Savitri; Ugroseno Yudho Bintoro; Made Putra Sedana; Muhammad Noor Muhammad; Pradana Zaky Romadhon; Putu Niken Ayu Amrita; Andi Yasmin Wijaya; Winona May Hendrata; Ami Ashariati Prayogo (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Carbohydrate antigens 15-3 (CA 15-3) is a conventional tumor marker in breast cancer, with low sensitivity and specificity. MicroRNA (miRNA)-21 showed its stability in circulation and could serve as powerful biomarker. The aim of this study was to evaluate miRNA-21 as breast cancer biomarker compared to CA 15-3 in Indonesian population.METHODS: Circulating plasma miRNA-21 expression was measured using qRT-PCR in 49 patients at various stages of breast cancer and 16 healthy controls. The relative expression value of miRNA-21 was calculated using 2-ΔΔCt. Meanwhile, CA 15-3 was quantified using electrochemiluminescence immunoassay (ECLIA) methods. The results of miRNA-21 and CA 15-3 plasma circulating expression were compared with controls at each stage and between stages of breast cancer.RESULTS: CA 15-3 median level in breast cancer group was 1.60 times higher compared to control group (p=0.019), 21.00 m/mL and 13.05 m/mL, respectively. Median miRNA-21 expression in breast cancer group was elevated 4.92 folds compared to control group (p=0.001), 4.43 and 0.90, respectively. There was no significant difference of CA 15-3 level between controls and all stages of breast cancer group. CA 15-3 cut-off value was 15.05 m/mL (p=0.016) with 59.2% sensitivity and 62.5% specificity. Meanwhile, there was a significant difference of miRNA-21 expression between controls and most stages of breast cancer group. Circulating miRNA-21 expression cut-off value was 2.07 (p=0.000) with 91.8% sensitivity and 87.5% specificity.CONCLUSION: Circulating miRNA-21 expression and CA 15-3 levels were significantly increased in breast cancer group compared to control group. The miRNA-21 expression increased consistently with breast cancer stage progression. miRNA-21 could serve as superior biomarker compared to CA 15-3.KEYWORDS: biomarker, breast cancer, circulating plasma, liquid biopsy, miRNA-21